2015
DOI: 10.1038/srep11602
|View full text |Cite
|
Sign up to set email alerts
|

MiR-19a regulates PTEN expression to mediate glycogen synthesis in hepatocytes

Abstract: MiR-19a, a member of mir-17-92 microRNA clusters, has been demonstrated to promote cell proliferation and angiogenesis via regulating the PI3K/AKT pathway, the major insulin signaling pathway. However, whether miR-19a plays an important role in glycogen synthesis in hepatocytes remains unknown. Here, we define the impact of miR-19a on glycogen synthesis and IL-6-induced reduced glycogenesis in hepatocytes and its underlying mechanisms. Our studies indicate that miR-19a was down-regulated in the livers of db/db… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…For example, miR-200s contributed to IL-6-induced insulin resistance in hepatocytes22. MiR-19a regulated PTEN expression to mediate glycogen synthesis in hepatocytes23. In addition, we demonstrated that the expression of miR-291b-3p was significantly upregulated in db/db and HFD-fed mice.…”
mentioning
confidence: 68%
“…For example, miR-200s contributed to IL-6-induced insulin resistance in hepatocytes22. MiR-19a regulated PTEN expression to mediate glycogen synthesis in hepatocytes23. In addition, we demonstrated that the expression of miR-291b-3p was significantly upregulated in db/db and HFD-fed mice.…”
mentioning
confidence: 68%
“…Aberrant PTEN expression or activation has been reported in many cancer types [28,29]. Moreover, miRNAs were also identified as novel regulators for PTEN, and these miRNAs include miR-19a [30], miR-21 [31], miR-26a [32], and miR-214 [33]. It is notable that overexpression of these PTEN-targeting miRNAs targeting was considered as a contributing factor for tumor development in these reports [32].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of PTEN expression and activation has been reported in many cancers (Li et al, 1997;Chen et al, 2005). Several miRNAs, such as miR-19a (Dou et al, 2015), miR-21 (Qi et al, 2009), miR-26a (Huse et al, 2009), and miR-214 (Schwarzenbach et al, 2012) have been identified as regulators of PTEN expression. In these reports, overexpression of miRNAs targeting PTEN has been considered a contributing factor for tumor development (Huse et al, 2009).…”
Section: Discussionmentioning
confidence: 99%